2020
DOI: 10.2196/16441
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of Participant-Centric Initiatives for Medical Research in the United States, the United Kingdom, and Japan: Scoping Review

Abstract: Background Information and communication technology (ICT) has made remarkable progress in recent years and is being increasingly applied to medical research. This technology has the potential to facilitate the active involvement of research participants. Digital platforms that enable participants to be involved in the research process are called participant-centric initiatives (PCIs). Several PCIs have been reported in the literature, but no scoping reviews have been carried out. Moreover, detailed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Additionally, the RUDY project demonstrated that digital technologies facilitate dialog and collaboration between patients and researchers [ 5 - 7 ]. This type of active patient involvement encouraged by digital tools is referred to as participant-centric initiatives [ 8 , 9 ]. Another research area where ICT use is expected to bring about significant change is human genome research.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the RUDY project demonstrated that digital technologies facilitate dialog and collaboration between patients and researchers [ 5 - 7 ]. This type of active patient involvement encouraged by digital tools is referred to as participant-centric initiatives [ 8 , 9 ]. Another research area where ICT use is expected to bring about significant change is human genome research.…”
Section: Introductionmentioning
confidence: 99%